EFFECTS OF TEMPERATURE AND NUTRIENT FEED ON THE PRODUCTION OF OXALIC ACID BY ASPERGILLUS NIGER - SRI HANDAYANI (Indonesian Mining Journal, 2011)
Oxalic acid is an important organic material used for rare earth metal extraction precipitator, metallic equip- ment purificant and purification of industrial minerals. Aspergillus niger is known to be able to produce a high concentration of oxalic acid using glucose as carbon and energy sources. For further process optimiza- tion, submerged fermentation experiments were carried out to study the effect of temperature and nutrient feed on the production of oxalic acid from medium containing glucose 35g/L. An increase in temperature process from 25 to 30°C allowed the productivity to significantly increase from 75.50 to 81.06% of theoretical yield with a final oxalic acid concentration of 17.04 g/L reached after 9 days of process. When operating at more controlled fermentor with fed-batch system, both productivity and oxalic acid concentration were markedly improved (88.01% of theoretical yield and 19.52 g/L respectively). The later system gave excel- lent yield almost 90% of theoretical yield as a prerequisite of economical value.